Efficient removal of crystal violet by diatomite and carbon in the fixed bed column: influence of different glucose/diatomite. Issue 56 (25th May 2016) - Zhang, Yanzhuo; Li, Jun; Cheng, Xiaojie; Bian, Wei; Chen, Guanghui; Li, Yun; Li, Wenjing; Zheng, Zhaoming
Abstract : This study investigated the way in which the modified adsorbent diatomite earth and glucose (DE & C) content affects the removal of crystal violet (CV) from water using a fixed bed column during hydrothermal carbonization. Abstract : This study investigated the way in which the modified adsorbent diatomite earth and glucose (DE & C) content affects the removal of crystal violet (CV) from water using a fixed bed column during hydrothermal carbonization. Fourier transform infrared spectroscopy results demonstrated the importance of functional groups (carbonyl and amino) during CV adsorption. The calculations showed the particle strength of DE & C was excellent. Scanning electron microscope images, energy dispersive spectrometry, Brunauer–Emmett–Teller analysis and Barrett–Joyner–Halenda analysis showed where the carbon species and pore structure provided highly favorable adsorption conditions. These characteristics indicated that DE & C is an excellent porous adsorbent. Five different levels of glucose content in the DE & C were tested in the fixed bed column. Because of differences in adsorption capacity, as the breakthrough time increased, the trend line changed from a straight line to an arc at C t / C 0 = 0–0.1. The best adsorption capacity was reflected by the related breakthrough time, but there was little change between different saturation times. Based on the calculated data, the optimal glucose/diatomite ratio was found to be 6/5, where the excessive carbon molecules blocked adsorbent bind sites in the sample. The Thomas model was used to determine the kinetics of CV column adsorption. When the CV concentration was 200 mg L −1, the flow rate was 7.5 mL min −1, the height was 5 cm, and the Thomas model showed that the maximum adsorption capacity ( q 0 ) was 87.05 mg g −1 . Disparities in the slopes of the bed depth service time (BDST) models showed that the initial adsorption efficiency was better than the later adsorption on the DE & C. The column packing was viable for five adsorption–elution cycles.